Progress in the Sputtering Preparation of Hf0.5Zr0.5O2 Ferroelectric Films and Memories - Kun Chen; Dan Zheng; Jie Gao; Hao Wang; Baoyuan Wang (Advanced Materials Interfaces)
Abstract Since the first report of ferroelectric HfO2 in 2011, researchers are making rapid progress in the understanding of both material properties and applications. Due to its compatibility with complementary metal oxide semiconductor, high coercivity voltage and the fact that ultrathin films remain ferroelectric, it is developed for applications in non‐volatile memories for data storage in different polarization states. As the most representative hafnium‐based ferroelectric materials, Hf0.5Zr0.5O2 has received a great deal of attention due to its various of outstanding properties. Magnetron sputtering is a promising method for the preparation of ferroelectric HfO2 films. This paper reviews recent developments in preparing Hf0.5Zr0.5O2 ferroelectric films and memories. Meanwhile, due to the many advantages of sputtering, such as higher throughputs, low cost and no carbon contamination, this review mainly focused on the preparation of Hf0.5Zr0.5O2 ferroelectric thin films by sputtering and explored its working mechanism and optimization strategy. In addition, the factors affecting the reliability of the memories, the mechanism of action, the solution ideas are introduced. These provide the basis for the design and optimization of Hf0.5Zr0.5O2 ferroelectric films and memories.